Analysis of Russian and Japanese Background Factors in Railway Construction in Eastern Province of China - Xiao , Hong (Journal of Theory and Practice of Social Science, 2023)
The railway construction in Eastern province of China was an important event in the early 20th century, which had a profound impact on the relations between China and the major countries in Northeast Asia, especially on the formulation and implementation of domestic and foreign policies of Russia and Japan, and laid the foreshadowing for the expansion of the East and the West in Northeast Asia in the future. This paper makes a comparative study of the position, foreign policy, strategic adjustment and treaty signed by China, Russia and Japan on the railway construction in Eastern province of China in the early 20th century. Through detailed historical data analysis and background interpretation, the paper tries to analyze the complex and profound reasons behind the railway construction, and explains the far-reaching impact of the development of Sino-Russian and Sino-Japanese relations before and after the railway construction in Eastern province of China.